Facebook Activity of Oklahoma Agritourism Facebook Pages - Brittany L Bowman; Quisto Settle; Stacy Tomas; Angel Riggs (Journal of Applied Communications, 2020)
Agritourism is recreational travel for agricultural activities. Agricultural operations benefit from income diversification, the public receives hands-on agricultural experiences, and rural communities benefit from economic development. However, agritourism operators have reported challenges in marketing. As social media becomes increasingly important in tourism marketing, the purpose of this research is to describe overall Facebook activity related to Oklahoma agritourism. A quantitative content analysis was conducted on 174 Facebook pages of Oklahoma agritourism operations to describe posts, public interaction, events, and advertisements. Oklahoma agritourism operations had a mean of 1,330 page likes, and 69% of Facebook pages had posts during the sample period of June 2018. Pages with at least one post had more than three times the number of page likes as pages without any posts. Amongst variables compared, user-generated content in the form of community posts and reviews had the strongest influence on overall page likes. Overall Facebook activity did not influence the number of people who were interested in an event, but there was a relationship between the number of people interested and timing of event posts. Additionally, pages with advertisements had more overall page likes but posted fewer times. Agritourism operators should encourage user-generated content, develop events, create at least one post, and consider sponsoring Facebook advertisements. Future research should describe post content, further explore the relationship of Facebook activity to overall page likes, and consider a sampling period outside of June to accommodate the possibility of seasonal fluctuations.
Keywords: Facebook; agritourism; content analysis; marketing; social media